THE IMPORTANCE OF TEACHING MORAL VALUES TO THE STUDENTS - Nurlaela Sari (Journal of English and Education, 2013)
Debating whether moral values are important to be taught or not is the wrong issue. Moral values have to be taught to the students to decrease a moral decadence. The question is how to teach moral values to the students. Education is the best way to teach moral values to the students. Education needs educators or teachers and strategies to deliver the materials. The strategies can be Character Building program in which the activities are arranged to increase the students’ emotional quotient, Caring School Community in which the activities are arranged to create a caring relationship between teachers-students, and Integrative Ethical Education model which has five steps for moral character development (supportive climate, ethical skills, apprenticeship instruction, self-regulation and adopting a developmental system approach). And the teachers should have four basic principles in teaching at the class such as Amanah, Rahmah, Taadubah and Sillah (calledReligiulitas Profesional). Keywords:Moral, values, education, teaching, character building